Community Response to Locational Conflict - Katolyk, Orest (My University, 1984)
In recent years, community interest groups have played an integral role in conflict situations. This paper focuses on community response to locational conflict and the community's role in the process of conflict resolution. A conceptual model of locational conflict is developed. The model includes three essential elements. These are (i) community perceptions of a facility, (ii) the formation of a community group and (iii) a cycle of conflict. This framework leads to a hypothesis that there exists a cycle of conflict between community response to locational conflict and conflict resolution. Specifically, as a conflict evolves there exists a cyclical repetition of stages which lead to a cycle of conflict. As an empirical example of locational conflict, the Upper Ottawa Street Landfill is used to evaluate the validity of the model. Illegal chemical dumping in the past has created an environmental conflict for the surrounding community. The analysis illuminated the hypothesis that a cycle of conflict exists between community response to locational conflict and conflict resolution.
Keywords: locational conflict; community response; chemical dumping; conflict resolution